Interpenetrating polymer networks for stitchable flexible materials
By using synthetic bioink 3D printing interpenetrating polymer networks in organ additive manufacturing, the problem of difficulty in developing sewnable flexible hydrogel materials in the prior art is solved, and efficient 3D printing and application of flexible hydrogel materials is achieved.
Patent Information
- Application Number
- CN202380067368.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-07-26
- Publication Date
- 2025-04-25
Smart Images

Figure BDA0005319450160000101 
Figure BDA0005319450160000111 
Figure BDA0005319450160000121
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Application No. 63 / 392,250, filed on July 26, 2022, which is incorporated herein by reference in its entirety. Technical Field
[0002] The present application relates to 3D printed structures, namely, interpenetrating polymer networks (IPNs) for 3D printing of sutureable flexible hydrogel materials. background
[0003] Interpenetrating polymer networks (IPNs) allow for the development of hydrogel materials that can be sutured and manipulated (e.g., bent, twisted, flexed) without breaking, as well as hydrogel materials that can be used for perfusion and ventilation.
[0004] There is a need for 3D-printable IPNs as sutureable flexible hydrogel materials for additive manufacturing of organs. Overview
[0005] The systems and methods of the present disclosure include interpenetrating polymer networks (IPNs) 3D printed using synthetic bio-inks for sutureable flexible hydrogel materials.
[0006] In an embodiment, an advanced manufactured interpenetrating polymer network (AM-IPN) comprises: a primary polymer network; a secondary polymer network, wherein the secondary polymer network is bonded to the primary polymer network via one or more crosslinks. In an embodiment, one or more of the primary polymer network, the secondary polymer network, and the one or more crosslinks are printed using synthetic bio-ink.
[0007] In an embodiment, the synthetic bio-ink comprises one or more of: HPA, about 5% to about 20%, and any range or value therebetween; PEGDA6000, about 5% to about 20%, and any range or value therebetween; TMPTA912, about 0.5% to about 3%, and any range or value therebetween; NAP, about 0.5% to about 3%, and any range or value therebetween; UV386A, about 0.1% to about 0.5%, and any range or value therebetween; polymer, about 0.001% to about 2.0%, and any range or value therebetween; and water, in an amount as the balance.
[0008] In an embodiment, the polymer comprises one or more of polyethylene oxide (PEO), polyethylene imine (PEI), polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), and combinations thereof.
[0009] In embodiments, the polymer is PEO and has a molecular weight of about 100,000 to about 4,000,000, and any range or value therebetween.
[0010] In embodiments, the polymer is PEO and is present in an amount from about 0.005% to about 1%, and any range or value therebetween.
[0011] In embodiments, the polymer is PEI having a molecular weight of about 25,000 to about 75,000, and any range or value therebetween.
[0012] In embodiments, the polymer is PEI and the amount is from about 0.005% to about 1%, and any range or value therebetween.
[0013] In embodiments, the polymer is PVP having a molecular weight of about 1,000,000 to about 1,300,000, and any range or value therebetween.
[0014] In embodiments, the polymer is PVP and is present in an amount from about 0.005% to about 2%, and any range or value therebetween.
[0015] In an embodiment, the polymer is PVA having a molecular weight of about 89,000 to about 98,000, and any range or value therebetween.
[0016] In embodiments, the polymer is PVA and is present in an amount from about 0.005% to about 2%, and any range or value therebetween.
[0017] In an embodiment, the synthetic bio-ink comprises one or more of: HPA in an amount of about 5% to about 20%, and any range or value therebetween; PEGDA 3400 in an amount of about 5% to about 20%, and any range or value therebetween; NAP in an amount of about 0.5% to about 3%; UV386A in an amount of about 0.1% to about 0.5%, and any range or value therebetween; polymer in an amount of about 0.001% to about 2.0%, and any range or value therebetween; and water in an amount as the balance.
[0018] In an embodiment, the polymer comprises one or more of polyethylene oxide (PEO), polyethylene imine (PEI), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), and combinations thereof.
[0019] In embodiments, the polymer is PEO and has a molecular weight of about 100,000 to about 4,000,000, and any range or value therebetween.
[0020] In embodiments, the polymer is PEO and is present in an amount from about 0.005% to about 1%, and any range or value therebetween.
[0021] In embodiments, the polymer is PEI having a molecular weight of about 25,000 to about 75,000, and any range or value therebetween.
[0022] In embodiments, the polymer is PEI and the amount is from about 0.005% to about 1%, and any range or value therebetween.
[0023] In embodiments, the polymer is PVP having a molecular weight of about 1,000,000 to about 1,300,000, and any range or value therebetween.
[0024] In embodiments, the polymer is PVP and is present in an amount from about 0.005% to about 2%, and any range or value therebetween.
[0025] In an embodiment, the polymer is PVA having a molecular weight of about 89,000 to about 98,000, and any range or value therebetween.
[0026] In embodiments, the polymer is PVA and is present in an amount from about 0.005% to about 2%, and any range or value therebetween.
[0027] In an embodiment, a method for preparing an advanced manufactured interpenetrating polymer network (AM-IPN) includes: printing one or more of a primary polymer network, a secondary polymer network, and one or more crosslinks using synthetic bio-ink and 3D printing technology; and assembling and / or printing the AM-IPN to form an assembled AM-IPN.
[0028] In an embodiment, the synthetic bio-ink comprises one or more of the following: polyethylene oxide (PEO), polyethylene imine (PEI), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), and combinations thereof.
[0029] In an embodiment, the AM-IPN is heated at about 50 mW / cm 2 About 400mW / cm 2 and any ranges or values in between are printed.
[0030] In an embodiment, the synthetic bio-ink comprises polyethylene oxide (PEO) in an amount of about 0.005% to about 1%, and any range or value therebetween, and the AM-IPN is heated at 50 mW / cm 2 About 300mW / cm 2 , and any range or value in between to print.
[0031] In an embodiment, the synthetic bio-ink comprises polyethyleneimine (PEI) in an amount of about 0.005% to about 1%, and any range or value therebetween, and the AM-IPN is heated at about 150 mW / cm 2 About 300mW / cm 2 and any ranges or values in between are printed.
[0032] In an embodiment, the synthetic bio-ink comprises polyvinylpyrrolidone (PVP) in an amount of about 0.005% to about 2%, and any range or value therebetween, and the AM-IPN is heated at about 50 mW / cm 2 About 300mW / cm 2 and any ranges or values in between are printed.
[0033] In an embodiment, the synthetic bio-ink comprises polyvinyl alcohol (PVA) in an amount of about 0.005% to about 2%, and any range or value therebetween, and the AM-IPN is heated at about 100 mW / cm 2 About 300mW / cm 2 and any ranges or values in between are printed.
[0034] In an embodiment, the 3D printing technology is one or more of digital light projection printing (DLP), stereolithography (SLA) printing technology, extrusion 3D printing technology or selective laser sintering 3D printing technology, or a combination thereof.
[0035] In an embodiment, the 3D printing technology is digital light printing (DLP) printing technology.
[0036] In an embodiment, a method of using an advanced manufactured interpenetrating polymer network (AM-IPN) comprises: modifying the surface of the AM-IPN to attach small airway epithelial cells (SAEC) to form a modified AM-IPN. In an embodiment, the method further comprises: using the modified AM-IPM for perfusion and ventilation.
[0037] Those skilled in the art will appreciate that this summary is illustrative only and is not intended to be limiting in any way. Other aspects, creative features and advantages of the devices and / or programs described herein (limited only by the claims) will become apparent in the detailed description set forth herein and in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] This patent or application file contains at least one drawing printed in color. Copies of this patent or patent application publication with color drawing(s) will be provided by the United States Patent and Trademark Office upon request and payment of the necessary fee.
[0039] The details of one or more embodiments of the subject matter described in this specification are set forth in the accompanying drawings and the description below. Other features, aspects, and advantages of the subject matter will become apparent from the description, drawings, and claims.
[0040] Figure 1A The interpenetrating polymer network in the synthetic AA42 bioink containing 8% PEGDA 3400 is shown, showing a high cross-linking density;
[0041] Figure 1B The interpenetrating polymer network in the synthetic AI28 bioink containing 5% PEGDA 6000 and 3% triacetate is shown, showing a moderate cross-linking density;
[0042] Figure 1C The interpenetrating polymer network in the synthetic 602 bioink containing 5% PEGDA 6000 is shown, showing a low cross-linking density;
[0043] Figure 2A A photograph showing the air supply for a TA instrument equipped with an OmniCure light source and the TRIOS software package;
[0044] Figure 2B Shows Figure 2A Photo of the TA Instruments OmniCure Light Source.
[0045] Figure 2C-1 Shows Figure 2A-2B First screenshot of TA Instruments’ TRIOS software package showing the geometry icon under the experiment tab.
[0046] Figure 2C-2 Shows Figure 2A-2B A second screenshot of the TRIOS software package for TA Instruments showing the instrument tab.
[0047] Figure 2C-3 Shows Figure 2A A third screenshot of the TA Instruments TRIOS software package shows the inertia (calibration) and oscillatory (new mapping) settings under the instrument tab.
[0048] Figure 2C-4 Shows Figure 2A-2B Fourth screenshot of the TA Instruments TRIOS software package showing the accessories settings under the Calibration tab.
[0049] Figure 2C-5 Shows Figure 2A-2B Fifth screenshot of the TA Instruments TRIOS software package showing the Geometries tab.
[0050] Figure 2C-6 Shows Figure 2A-2B Sixth screenshot of the TA Instruments TRIOS software package showing condition options and settings.
[0051] Figure 2C-7 Shows Figure 2A-2B The seventh screenshot of the TA Instruments TRIOS software package shows the otherevent UV settings.
[0052] Figure 2C-8 Shows Figure 2A-2B Eighth screenshot of TA Instruments’ TRIOS software package showing the oscillation fast sampling settings.
[0053] Figure 2D A graph showing the step time (Step Time) ts (s) vs. storage modulus G' (kPa) of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in the synthesis of AL35, AL36, AL37, and AL38 bioinks;
[0054] Figure 3A The air supply for a DMA 850 instrument equipped with the TRIOS software package is shown. The air supply to the DMA instrument should be approximately 60 psi;
[0055] Figure 3B shows the calibration Figure 3A Photo of the bottom fixture of the DMA 850 instrument;
[0056] Figure 3CShows Figure 3A-3B First screenshot of the TRIOS software package for the DMA 850 instrument, showing the Clamp Calibration tab;
[0057] Figure 3D Shows the assembly Figure 3A-3B Photo of the bottom of the compression device of the DMA 850 instrument;
[0058] Figure 3E Shows the Figure 3A-3B Photo of the top and bottom fixtures of the DMA instrument aligned;
[0059] Figure 3F Shows Figure 3A-3B and Figure 3D-Figure 3E A second screenshot of the TRIOS software package for the DMA 850 instrument showing the Clamp Calibration tab.
[0060] Figure 3G-1 shows a screen shot of a DMA 850 instrument showing the float icon;
[0061] Figure 3G-2 Shows Figure 3A-3B and Figure 3D-Figure 3E A third screenshot of the TRIOS software package for the DMA 850 instrument showing sampledimensions.
[0062] Figure 3G-3 Shows Figure 3A-3B and Figure 3D-Figure 3E Fourth screenshot of the TRIOS software package for the DMA 850 instrument showing the DMAControl tab;
[0063] Figure 3H Plots of strain (Strain) ε (%) vs stress (Stress) σε (kPa) for synthetic AA42, AL35 (0.5% PEO), AL36 (0.1% PEO), AA42, AL43 (0.5% PEO), AL44 (0.1% PEO), AL45 (0.05% PEO), and AI28 bioinks and advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) 4000000 in Lung G1 are shown, showing a comparison of PEO concentrations in the bioinks;
[0064] Fig. 3IPlots of strain ε (%) vs stress σε (kPa) for advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) 4000000 in synthetic AL35, AL36, and AA42 bioinks showing a comparison of PEO concentrations in the bioinks;
[0065] Figure 3J Plots of strain ε (%) vs stress σε (kPa) for advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL42, AL45, AI28 bioinks and Lung G1 showing a comparison of PEO concentrations in the bioinks;
[0066] Figure 3K Plots of strain ε (%) vs stress σε (kPa) for synthetic AL45 (3% triacrylate, 0.05% PEO), AL48 (4% triacrylate, 0.05% PEO), AL49 (3% triacrylate, 0.01% PEO) bioinks and advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) 4000000 in Lung G1 showing a comparison of PEO concentrations in the bioinks;
[0067] Figure 4A Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL35 bioink;
[0068] Figure 4B Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL36 bioink;
[0069] Figure 4C Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL37 bioink;
[0070] Figure 5 Plots showing strain ε (%) vs stress σε (kPa) of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL45 (energy 210 mJ), AL49 (energy 90 mJ), and AI28 (parent) (energy 48 mJ) bio-inks;
[0071] Fig. 6APhotographs of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL45 bioink (3% triacrylate, 0.05% PEO) showing 100.100 dense rings with an average vasculature thickness of 95.4 ± 8.7 μm;
[0072] Figure 6B Photographs of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL45 bioink are shown, showing 50.80 dense rings with an average vessel thickness of 48.8 ± 10.1 μm;
[0073] Fig. 7A Photographs of advanced fabricated interpenetrating polymer networks (AM-IPNs) in an advanced fabricated hydrogel material of synthetic AL49 bioink (3% triacrylate, 0.1% PEO) showing the hydrogel material placed in a bioreactor in preparation for perfusion and aeration;
[0074] Figure 7B Shows Fig. 7A Photographs of AM-IPNs in advanced fabricated hydrogel materials showing the hydrogel material after perfusion and during ventilation;
[0075] Fig. 8A Photographs showing biocompatibility testing of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL36 bioink (glass control);
[0076] Figure 8B Photographs showing biocompatibility testing (day 1) of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL36 bioink, demonstrating attachment of small airway epithelial cells (SAEC);
[0077] Figure 8C Photographs showing biocompatibility testing (day 4) of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL36 bioink, demonstrating reduced attachment of small airway epithelial cells (SAEC);
[0078] Fig.9A A photograph of a stitching test of an advanced manufactured interpenetrating polymer network (AM-IPN) of polyethylene oxide (PEO) in a synthetic AL48 (4% triacrylate, 0.05% PEO) bio-ink is shown, showing the high cross-linking density of the interpenetrating polymer network in the bio-ink;
[0079] Fig. 9BA photograph of a stitching test of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL49 (3% triacrylate, 0.1% PEO) bioink is shown, showing the moderate crosslinking density of the interpenetrating polymer networks in the bioink;
[0080] Fig.10 Plots showing step time ts (s) vs storage modulus G' (kPa) of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in synthetic AL60, AL62, AL364, AL65, and AL66 bioinks;
[0081] Fig.11 The synthetic AL60 (power 50mW / cm 2 , time is 1900ms), AL62 (power is 50mW / cm 2 , time is 750ms), AL62 (power is 150mW / cm 2 , time is 500ms), AL62 (power is 200mW / cm 2 , time 500ms) bioink and advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) 750,000 in Lung G1;
[0082] Fig. 12A Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in synthetic AL60 bioink;
[0083] Fig. 12B is a photograph of the advanced fabricated interpenetrating polymer network (AM-IPN) of polyethyleneimine (PEI) in the synthetic AL61 bioink;
[0084] Fig. 12C It is synthetic AL62 (power 50mW / cm 2 ) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in bio-ink, showing the low cross-link density of the interpenetrating polymer networks of PEI in bio-ink;
[0085] Fig.12D It is synthetic AL62 (150mW / cm 2 ) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in bio-ink, showing the low cross-link density of the interpenetrating polymer networks of PEI in bio-ink;
[0086] Fig.12EIt is synthetic AL62 (200mW / cm 2 ) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in bio-ink, showing the low cross-link density of the interpenetrating polymer networks of PEI in bio-ink;
[0087] Fig.13A The synthetic AL62 (power 50mW / cm 2 , time 750ms) Photo of stitching test of advanced manufactured interpenetrating polymer network (AM-IPN) of polyethyleneimine (PEI) in bio-ink, showing the low cross-linking density of interpenetrating polymer network of PEI in bio-ink;
[0088] Fig. 13B The synthetic AL62 (power 100mW / cm 2 , time 500ms) Photo of stitching test of advanced manufactured interpenetrating polymer network (AM-IPN) of polyethyleneimine (PEI) in bio-ink, showing the low cross-linking density of interpenetrating polymer network of PEI in bio-ink;
[0089] Fig. 13C The synthetic AL62 (power 150mW / cm 2 , time 450ms) Photo of stitching test of advanced fabricated interpenetrating polymer network (AM-IPN) of polyethyleneimine (PEI) in bio-ink, showing the moderate cross-linking density of interpenetrating polymer network of PEI in bio-ink;
[0090] Fig.13D The synthetic AL62 (power 200mW / cm 2 , time 400ms) Photo of stitching test of advanced fabricated interpenetrating polymer network (AM-IPN) of polyethyleneimine (PEI) in bio-ink, showing the moderate cross-linking density of interpenetrating polymer network of PEI in bio-ink;
[0091] Fig.14 Plots of step time ts (s) vs storage modulus G' (kPa) of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinyl pyrrolidone (PVP) in synthetic AL68, AL69, AL70, AL72, AL73, AL74, and AL 75 bioinks are shown;
[0092] Fig.15Plots of strain ε (%) vs stress σε (kPa) for synthetic AL68 (3% triacrylate, 0.5% PVP), AL70 (3% triacrylate, 0.05% PVP), AL72 (2% triacrylate, 1% PVP), AL73 (2% triacrylate, 0.5% PVP), AL74 (2% triacrylate, 0.1% PVP) bioinks and advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl pyrrolidone (PVP) in Lung G1 are shown;
[0093] Fig.16A Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL68 bioink;
[0094] Fig. 16B is a photograph of the advanced manufactured interpenetrating polymer network (AM-IPN) of polyvinylpyrrolidone (PVP) in the synthetic AL70 bioink;
[0095] Fig. 16C is a photograph of the advanced manufactured interpenetrating polymer network (AM-IPN) of polyvinylpyrrolidone (PVP) in the synthetic AL72 bioink;
[0096] Fig.16D is a photograph of the advanced manufactured interpenetrating polymer network (AM-IPN) of polyvinylpyrrolidone (PVP) in the synthetic AL73 bioink;
[0097] Fig.16E is a photograph of the advanced manufactured interpenetrating polymer network (AM-IPN) of polyvinylpyrrolidone (PVP) in the synthetic AL74 bioink;
[0098] Fig.17A A photograph showing the stitching test of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL68 bioink;
[0099] Fig. 17B A photograph showing the stitching test of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL70 bioink;
[0100] Fig. 17C A photograph showing the stitching test of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL73 bioink;
[0101] Fig.18Plots showing step time ts (s) vs storage modulus G' (kPa) of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in synthetic AL76 and AL 77 bioinks;
[0102] Fig.19 Plots showing strain ε (%) vs stress σε (kPa) for advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in synthetic AL76, AL77 bioinks, and Lung G1;
[0103] Fig. 20A The synthesis of AL76 (power 50mW / cm 2 , time 1000ms) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink, showing the low cross-linking density of the interpenetrating polymer networks of PVA in bio-ink;
[0104] Fig. 20B The synthetic AL76 (power 100mW / cm 2 , time 700ms) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink, showing low to moderate cross-linking density of the interpenetrating polymer networks of PVA in bio-ink;
[0105] Fig. 20C The synthetic AL77 (power 100mW / cm 2 , time 700ms) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink, showing the moderate cross-linking density of the interpenetrating polymer networks of PVA in bio-ink;
[0106] Fig.21A The synthesis of AL76 (power 50mW / cm 2 , time 1000ms) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink, showing the low cross-linking density of the interpenetrating polymer networks of PVA in bio-ink;
[0107] Fig.21B The synthesis of AL76 (power 50mW / cm 2 , time 2500ms) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink, showing low to moderate cross-linking density of interpenetrating polymer networks of PVA in bio-ink;
[0108] Fig. 21C The synthetic AL76 (power 100mW / cm2 , time 700ms) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink, showing the moderate cross-linking density of the interpenetrating polymer networks of PVA in bio-ink;
[0109] Fig.22A The synthetic AL76 (power 100mW / cm 2 , time 700ms) Photo of the stitching test of the advanced manufactured interpenetrating polymer network (AM-IPN) of polyvinyl alcohol (PVA) in bio-ink, showing the moderate cross-linking density of the interpenetrating polymer network of PVA in the bio-ink;
[0110] Fig. 22B The synthetic AL77 (power 100mW / cm 2 , time 700ms) Photo of the stitching test of the advanced manufactured interpenetrating polymer network (AM-IPN) of polyvinyl alcohol (PVA) in bio-ink, showing the moderate cross-linking density of the interpenetrating polymer network of PVA in the bio-ink;
[0111] Fig.23A Graph showing stress (kPa) of polyvinyl pyrrolidone (PVP) in synthetic AW55, AW99, and AI28 bioinks;
[0112] Fig. 23B Graph showing the strain (%) of polyvinyl pyrrolidone (PVP) in synthetic AW55, AW99, and AI28 bioinks;
[0113] Fig.23C A graph showing the Young's modulus (kPa) of polyvinylpyrrolidone (PVP) in synthetic AW55, AW99, and AI28 bioinks; and
[0114] Fig.24 A photograph of a hydrogel (dogbone) material is shown. Detailed Description
[0115] The following detailed description of various embodiments of the present invention refers to the accompanying drawings, which illustrate specific embodiments in which the present invention can be practiced. Although the exemplary embodiments of the present invention have been described in detail, it should be understood that various other modifications will be apparent to those skilled in the art without departing from the spirit and scope of the present invention, and these modifications can be easily made by those skilled in the art. Therefore, the scope of the appended claims is not limited to the examples and descriptions described herein, but the claims should be interpreted as covering all features of the patentable novelty in the present invention, including all features that are considered to be equivalent to those skilled in the art of the present invention. Therefore, the scope of the present invention is limited only by the appended claims and the full scope of equivalents enjoyed by these claims. Advanced Manufacturing Interpenetrating Polymer Networks (AM-IPN)
[0116] Interpenetrating polymer networks are primary networks connected to secondary networks through non-covalent bonds.
[0117] Figure 1A The interpenetrating polymer network in the synthetic AA42 bio-ink containing 8% PEGDA 3400 is shown, demonstrating the high cross-linking density of the interpenetrating polymer network in the bio-ink.
[0118] Figure 1B The interpenetrating polymer network in the synthetic AI28 bioink containing 5% PEGDA 6000 and 3% triacetate is shown, showing the moderate cross-linking density of the interpenetrating polymer network in the bioink.
[0119] Figure 1C The interpenetrating polymer network in the synthetic 602 bio-ink containing 5% PEGDA 6000 is shown, demonstrating the low cross-linking density of the interpenetrating polymer network in the bio-ink.
[0120] Any suitable synthetic bio-ink may be used. For example, suitable synthetic bio-inks include, but are not limited to, the AA42, AI15, AI28, and AJ55 bio-inks described herein.
[0121] Exemplary Bio-inks
[0122] AA42 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA3400 7.6-8.4 LAP 0.95-1.05 UV386A 0.114-0.126 water 76.84-84.92 total 100
[0123] AI15 Bio-ink
[0124] AI28 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TMPTA912 2.85-3.15 NAP 1.52-1.68 UV386A 0.152-0.168 water 76.23-84.25 total 100
[0125] AJ55 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TMPTA912 1.9-2.1 NAP 0.95-1.05 UV386A 0.171-0.189 water 76.78-84.86 total 100
[0126] Any suitable polymer can be incorporated into the synthetic bio-ink. For example, suitable polymers include, but are not limited to, polyethylene oxide (PEO), polyethylene imine (PEI), polyvinyl pyrrolidone (PVP), and polyvinyl alcohol (PVA).
[0127] Exemplary polymers Example bio-ink formulation and printing settings for the FS20 DLP 3D System printer
[0128] Polyethylene oxide (PEO)
[0129] In these examples, polyethylene oxide (PEO) polymer was incorporated into AA42 bioink (stock solution) as shown below.
[0130] Polyethylene oxide 4000000 (0.5% PEO stock solution)
[0131] Polyethylene oxide 4000000 polymer was added to water, heated at 100 °C, and mixed at 600 RPM before being incorporated into the bio-ink.
[0132] Polyethylene oxide 1000000 (0.5% PEO stock solution)
[0133] Polyethylene oxide 1000000 polymer was added to water, heated at 100 °C, and mixed at 600 RPM before being incorporated into the bio-ink.
[0134] AA42 bio-ink (stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA3400 7.6-8.4 LAP 0.95-1.05 UV386A 0.114-0.126 water 17.04-18.84 total 35.21-38.91
[0135] In the AA42 bio-ink (stock) solution, the water concentration was slightly reduced (compared to AA42 bio-ink) to allow the addition of polyethylene oxide polymer stock solution to prepare AL35, AL36, AL37, AL38, and AL39 bio-inks.
[0136] AL35 Bio-ink
[0137] AL36 Bio-ink
[0138] AL37 Bio-ink
[0139] AL38 Bio-ink
[0140] AL39 Bio-ink
[0141] AL42 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TAC 2.85-3.15 NAP 1.52-1.68 UV386A 0.152-0.168 water 75.75-83.73 PEI25000 25000 0.475-0.525 total 100
[0142] AL43 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TAC 0.95-1.05 NAP 1.52-1.68 UV386A 0.152-0.168 water 75.75-83.73 PEO40000000 4000000 0.048-0.053 total 100
[0143] AL44 Bio-ink
[0144] AL45 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TAC 2.85-3.15 NAP 1.52-1.68 UV386A 0.152-0.168 water 75.75-83.73 PEO40000000 4000000 0.048-0.053 total 100
[0145] AL47 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 4.75-5.25 PEGDA700 2.85-3.15 PEGDA6000 4.75-5.25 NAP 1.43-1.58 UV386A 0.152-0.168 water 81.07-89.61 total 100
[0146] AL48 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TAC 3.8-4.2 NAP 1.52-1.68 UV386A 0.152-0.168 water 75.75-83.73 PEO40000000 4000000 0.048-0.053 total 100
[0147] Rheological testing
[0148] Figure 2A A photograph of the air supply for a TA instrument equipped with an OmniCure light source and the TRIOS software package is shown. The air supply to the TA instrument should be approximately 20 psi to 40 psi air.
[0149] Figure 2B Shows Figure 2A Photo of the TA Instruments OmniCure Light Source.
[0150] Figure 2C-1 Shows Figure 2A-2B First screenshot of the TA Instruments TRIOS software package, showing the geometry icon under the experiment tab.
[0151] Figure 2C-2 Shows Figure 2A-2B A second screenshot of the TA Instruments TRIOS software package showing the instrument tab; and Figure 2C-3 Shows Figure 2A A third screenshot of the TA Instruments TRIOS software package showing the inertia (calibration) and oscillatory (new mapping) settings under the instrument tab.
[0152] In the inertia setting, the new calibration reading is accepted because it is acceptable (eg, close to the previous calibration reading).
[0153] In the oscillatory setting, calibrate the new mapping.
[0154] The light source is calibrated with the black shield of the UV radiometer placed on the surface of the light source where the sample can be placed.
[0155] Figure 2C-4 Shows Figure 2A-2B Fourth screenshot of TA Instruments' TRIOS software package showing the accessories settings under the Calibration tab. UV irradiation should be at 50%. To calibrate the light source, enter the value measured by the UV radiometer into the software (e.g., 56.2) and accept.
[0156] Figure 2C-5 Shows Figure 2A-2B Fifth screenshot of TA Instruments' TRIOS software package, showing the Geometries tab. The 20 mm parallel plate geometry is selected. The appropriate plates are placed on the rheometer.
[0157] In the inertia setting, accept the new calibration reading because it is acceptable (eg, close to the previous reading).
[0158] In the friction setting, accept the new calibration reading as it is acceptable (eg, close to the previous reading).
[0159] Lower the rheometer slightly above the sample placement and select the zero gap icon.
[0160] The rheometer was raised to the loading gap.
[0161] Under the Geometry tab, the gap was set to 200 μm and the minimum sample volume was set to 0.062 mL.
[0162] Figure 2C-6 Shows Figure 2A-2B Sixth screenshot of the TA Instruments TRIOS software package showing the condition options and settings.
[0163] Figure 2C-7 Shows Figure 2A-2B Seventh screenshot of the TA Instruments TRIOS software package, showing the otherevent UV settings.
[0164] Figure 2C-8 Shows Figure 2A-2B Eighth screenshot of the TA Instruments TRIOS software package showing the oscillation fast sampling settings.
[0165] 75 μL of sample was loaded into the center of the rheometer plate. Any bubbles were removed by gently poking with a needle. The gap was set to 200 μm. Before each experiment, the black UV shield was lowered to block UV light.
[0166] Figure 2D Shown is a graph of step time ts (s) vs storage modulus G' (kPa) for advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL35, AL36, AL37, and AL38 bioinks.
[0167] Rheological data of AL35, AL36, AL37 and AL38 bio-inks Bio-ink Start (onset) time (s) Storage modulus at 50s AL35 20 4.42 AL36 18.5 14.52 AL37 17.5 16.73 AL38 19 13.18
[0168] AL35, AL36, AL37 and AL38 Bio-Ink Printing Settings for FS20 DLP 3D System Printers
[0169] Compression test
[0170] Dynamic Mechanical Analysis (DMA) is a technique frequently used to characterize material properties as a function of atmosphere, frequency, stress, temperature, time, and combinations thereof.
[0171] Compression testing is performed using a DMA 850 instrument, which is designed to measure the viscoelastic properties (e.g., modulus, damping) of rigid and soft solid materials. Compression testing can be used to measure the properties of low to medium modulus materials (including gels and weak elastomers). The sample must withstand a static (preload) force during the compression test. The sample should have the highest possible thickness to diameter ratio, depending on sample preparation and instrument limitations.
[0172] A typical sample is a printed disc (eg, about 8 mm in diameter and about 3 mm thick).
[0173] The printed disc is mounted in a fixture, one part of which is fixed and the other part is connected to a drive motor and is movable. The motor applies deformation directly to the printed disc.
[0174] The compressive modulus is calculated from the slope of stress (kPa) versus strain (%) in the linear region, which is typically from 0% to 10% of the initial strain. To ensure that the slope is calculated in the linear region, the R of the modulus 2 The value should be between about 0.95 and about 0.99.
[0175] The compressive failure strength and strain are the values of the maximum stress (kPa) and maximum strain (%) at which the printed disk failed.
[0176] Figure 3A Shown is the air supply for a DMA 850 instrument equipped with the TRIOS software package.The air supply to the DMA instrument should be approximately 60 psi.
[0177] Figure 3B shows the calibration Figure 3A Photo of the bottom clamp of the DMA 850 instrument. The bottom clamp of the DMA instrument should be calibrated prior to compression testing. Install the bottom clamp onto the DMA instrument and tighten with the Allen key until the bottom clamp is aligned and stable.
[0178] Figure 3C Shows Figure 3A-3B First screenshot of the TRIOS software package for the DMA 850 instrument showing the Clamp Calibration tab. Turn off the furnace of the DMA instrument. Calibrate the mass of the bottom clamp and accept.
[0179] Figure 3D Shows the assembly Figure 3A-3B Photo of the bottom of the compression fixture of the DMA 850 instrument. After calibrating the mass of the bottom fixture, assemble the bottom of the compression fixture and tighten it into place with an Allen wrench.
[0180] Figure 3E Shows the Figure 3A-3B Photo of the top clamp of the DMA instrument aligned with the bottom clamp. After installing the base plate, align the top clamp with the bottom clamp and tighten it into place using the Allen key.
[0181] Figure 3F Shows Figure 3A-3B and Figure 3D-Figure 3E Second screenshot of the TRIOS software package for the DMA 850 instrument, showing the Clamp Calibration tab. Once the plate is perfectly aligned, calibrate the compliance of the clamp and accept. The compliance value should be less than 1 μN / m to be acceptable.
[0182] Figure 3G-1A screenshot of a DMA 850 instrument showing the float icon is shown. After setting up the fixture, the fixture should be calibrated. Press the float icon to float the top fixture. This ensures that the top fixture rests lightly on the printed disc.
[0183] The printed discs should be kept in 1X DPBS overnight before compression testing. Immediately before placing the printed discs into the jig, excess 1X DPBS should be gently blotted off using a Kimwipe.
[0184] Figure 3G-2 Shows Figure 3A-3B and Figure 3D-Figure 3E Third screenshot of the TRIOS software package for the DMA 850 instrument, showing the sampledimensions. The diameter and thickness of the printed disk were measured using a vernier caliper. The measurements were entered into the TRIOS software package.
[0185] Place the printed disc between the bottom clamp and the top clamp, making sure the printed disc is centered between the clamps. Lower the removable top clamp to lightly touch the printed disc.
[0186] Under the Procedure tab, the desired compression parameters (eg, ultimate strain percentage, strain rate) should be entered. Typical compression tests are conducted at approximately 20% strain / minute.
[0187] Figure 3G-3 Shows Figure 3A-3B and Figure 3D-Figure 3E Fourth screenshot of the TRIOS software package for the DMA 850 instrument, showing the DMAControl tab. Enter a 0.05N preload force for the printed disk (e.g., hydrogel). Compression testing can be performed with an open oven. Compression testing can be stopped once the printed disk begins to fail (e.g., break).
[0188] After the compression test is stopped, the Young's modulus can be calculated from the slope of the stress-strain curve in the linear region (e.g., about 0% to about 10% strain). The ultimate compressive strain (%) and strength (kPa) can be calculated at the failure point. The average of about six printed discs should be calculated to obtain the Young's modulus and failure strain.
[0189] Figure 3HPlots of strain ε (%) vs stress σε (kPa) of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) 4000000 in synthetic AA42, AL35 (0.5% PEO), AL36 (0.1% PEO), AA42, AL43 (0.5% PEO), AL44 (0.1% PEO), AL45 (0.05% PEO) and AI28 bioinks and Lung G1 are shown, showing a comparison of PEO concentrations in the bioinks.
[0190] Fig. 3I Plot of strain ε (%) vs stress σε (kPa) of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) 4000000 in synthetic AL35, AL36, and AA42 bioinks showing a comparison of PEO concentrations in the bioinks.
[0191] Figure 3J Plots of strain ε (%) vs stress σε (kPa) for advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in the synthesis of AL42, AL45, AI28 bioinks, and Lung G1, showing a comparison of PEO concentrations in the bioinks.
[0192] Figure 3K Plots of strain ε (%) vs stress σε (kPa) for the synthetic AL45 (3% triacrylate, 0.05% PEO), AL48 (4% triacrylate, 0.05% PEO), AL49 (3% triacrylate, 0.01% PEO) bioinks and advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) 4000000 in Lung G1, showing a comparison of PEO concentrations in the bioinks.
[0193] Figure 4A Photographs of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL35 bioink are shown.
[0194] Figure 4B Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL36 bioink.
[0195] Figure 4C Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL37 bioink.
[0196] AL35 Bio-Ink Compression Data Area under the curve Maximum strain% 2945.1 188.91 2751.15 170.74 3228.81 199.01 2152.97 134.12 2769.71 173.20
[0197] AL36 Bio-Ink Compression Data Area under the curve Maximum strain% 4910.25 308.44 2481.46 145.35 2655.55 150.95 3010.47 193.83 3078.87 181.54 2834.68 165.00 3161.88 190.85
[0198] Figure 5 Plots of strain ε (%) vs stress σε (kPa) of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL45 (energy 210 mJ), AL49 (energy 90 mJ), and AI28 (mother solution) (energy 48 mJ) bioinks are shown.
[0199] Fig. 6A Photographs of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL45 bioink (3% triacrylate, 0.05% PEO 4000000) are shown, showing 100.100 dense rings with an average vessel thickness of 95.4 ± 8.7 μm.
[0200] Figure 6B Photographs of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL45 bioink are shown, showing 50.80 dense rings with an average vessel thickness of 48.8 ± 10.1 μm.
[0201] Fig. 7A Photographs of advanced fabricated interpenetrating polymer networks (AM-IPNs) in an advanced fabricated hydrogel material of synthetic AL49 bioink (3% triacrylate, 0.1% PEO 4000000) showing the hydrogel material placed in a bioreactor in preparation for perfusion and aeration.
[0202] AL49 Bio-ink
[0203] The hydrogel material was placed in the bioreactor; and the tubes for the vasculature and airways were inserted through the blue lid of the bioreactor. This tested the ability of the hydrogel material to expand around the tubes.
[0204] Figure 7B Shows Fig. 7A Photographs of the AM-IPN in the advanced fabricated hydrogel material showing the hydrogel material after perfusion and during ventilation.
[0205] Biocompatibility testing
[0206] AL36 bio-ink printed disks (eg, hydrogels) (eg, about 8 cm in diameter and about 3 mm thick) were printed.
[0207] Small airway epithelial cells are seeded on the printed discs (e.g., hydrogels). This is performed in clear bottom cell culture plates.
[0208] At each time point, the printed disk (eg, hydrogel) is placed under a microscope to determine whether small airway epithelial cell attachment is still occurring and whether the small airway epithelial cells remain unstained.
[0209] Fig. 8A Photographs showing the biocompatibility testing of polyethylene oxide (PEO) in synthetic AL36 bio-ink (glass control).
[0210] Figure 8B Photographs showing biocompatibility testing (day 1) of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL36 bioink, demonstrating attachment of small airway epithelial cells (SAECs).
[0211] Figure 8C Photographs showing biocompatibility testing (day 4) of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL36 bioink, demonstrating reduced attachment of small airway epithelial cells (SAECs).
[0212] Suture test
[0213] Using a 45mm gauge needle, pass the needle through the solid portion of the advanced manufactured hydrogel material (capsulent). Inspect the hydrogel material (capsulent) for any cracking. The purpose of this test is to see if the hydrogel material can be sutured without cracking or unraveling.
[0214] Fig.9A A photograph of a stitching test of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL48 (4% triacrylate, 0.05% PEO) bioink is shown, demonstrating the high cross-linking density of the interpenetrating polymer networks in the bioink.
[0215] Fig. 9B A photograph of a stitching test of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethylene oxide (PEO) in synthetic AL49 (3% triacrylate, 0.1% PEO) bioink is shown, demonstrating the moderate cross-linking density of the interpenetrating polymer networks in the bioink.
[0216] The AL35 bioink swelled and disintegrated during the surface modification process. However, the AL36 bioink remained intact during the surface modification process but showed reduced attachment of small airway epithelial cells (SAEC) by day 4.
[0217] AA42 bio-ink can form an interpenetrating polymer network with high cross-linking density in the bio-ink. Therefore, the polyethylene oxide (PEO) polymer can be tightly combined in the interpenetrating polymer network.
[0218] Polyethyleneimine (PEI)
[0219] In these examples, polyethyleneimine (PEI) polymer was incorporated into AI28 bioink (stock solution) as shown below.
[0220] Polyethyleneimine (PEI) 750000 (50% PEI stock solution)
[0221] Polyethyleneimine (PEI) 750000 was dissolved in water and mixed at 600 RPM before adding the other components.
[0222] Polyethyleneimine (PEI) 25000 (50% PEI stock solution)
[0223] Polyethyleneimine (PEI) 25000 was dissolved in water and mixed at 600 RPM before adding other components.
[0224] AI28 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TMPTA912 2.85-3.15 NAP 1.52-1.68 UV386A 0.152-0.168 water 76.23-84.25 total 100
[0225] AL60 bio-ink (stock solution)
[0226] AL60 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) water 47.86-52.90 AL60 (stock solution) 47.14-52.10 total 100
[0227] AL61 Bio-ink
[0228] AL62 Bio-ink
[0229] AL63 Bio-ink
[0230] AL64 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) PEI25000 25000 PEI25000–408727 0.095-0.105 water 47.77-52.79 AL60 (stock solution) 47.14-52.10 total 100
[0231] AL65 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) PEI25000 25000 PEI25000–408727 0.048-0.053 water 47.81-52.85 AL60 (stock solution) 47.14-52.10 total 100
[0232] AL66 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) PEI25000 25000 PEI25000–408727 0.475-0.525 water 47.39-52.37 AL60 (stock solution) 47.17-52.10 total 100
[0233] Rheological testing
[0234] Rheological tests were as discussed above and Figure 2A-2C-8 shown.
[0235] Fig.10 Shown is a graph of step time ts (s) vs storage modulus G' (kPa) for advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in the synthesis of AL60, AL62, AL364, AL65, and AL66 bioinks.
[0236] Rheological data of AL60, AL62, AL64, AL65 and AL66 bio-inks Bio-ink Start time Storage modulus at 50s AL60 2.5 12.81 AL62 2.5 12.39 AL64 2.5 20.21 AL65 2.5 16.79 AL66 2.5 18.92
[0237] AL60 Bio-Ink Printing Settings on FS20 DLP 3D System Printer Grassroots B unit Regional layer E unit power 50 <![CDATA[mW / cm 2 ]]> power 50 <![CDATA[mW / cm 2 ]]> Exposure time 1500 ms Exposure time 1200 ms Pumping distance 300 μm Pumping distance 300 μm Run time 1500 ms Run time 1500 ms Run time interval 1500 ms Run time interval 1500 ms Downtime 1000 ms Downtime 1500 ms Downtime Interval 2000 ms Downtime Interval 2000 ms
[0238] AL61 Bio-Ink Printing Settings on FS20 DLP 3D System Printer Grassroots B unit Regional layer E unit power 50 <![CDATA[mW / cm 2 ]]> power 50 <![CDATA[mW / cm 2 ]]> Exposure time 1000 ms Exposure time 800 ms Pumping distance 300 μm Pumping distance 300 μm Run time 1500 ms Run time 1500 ms Run time interval 1500 ms Run time interval 1500 ms Downtime 1000 ms Downtime 1500 ms Downtime Interval 2000 ms Downtime Interval 2000 ms
[0239] FS20 DLP 3D system printer AL62 (50mW / cm 2 ) Bio-ink printing setup Grassroots B unit Regional layer E unit power 50 <![CDATA[mW / cm 2 ]]> power 50 <![CDATA[mW / cm 2 ]]> Exposure time 100 ms Exposure time 7500 ms Pumping distance 300 μm Pumping distance 300 μm Run time 1500 ms Run time 1500 ms Run time interval 1500 ms Run time interval 1500 ms Downtime 1000 ms Downtime 1500 ms Downtime Interval 2000 ms Downtime Interval 2000 ms
[0240] FS20 DLP 3D system printer AL62 (150mW / cm 2 ) Bio-ink printing setup
[0241] AL62 (200mW / cm2) bio-ink printing settings for FS20 DLP 3D system printer Grassroots B unit Regional layer E unit power 200 <![CDATA[mW / cm 2 ]]> power 200 <![CDATA[mW / cm 2 ]]> Exposure time 1000 ms Exposure time 500 ms Pumping distance 300 μm Pumping distance 300 μm Run time 1500 ms Run time 1500 ms Run time interval 1500 ms Run time interval 1500 ms Downtime 1000 ms Downtime 1500 ms Downtime Interval 2000 ms Downtime Interval 2000 ms
[0242] Expansion test
[0243] AL36 bio-ink printed disks (eg, hydrogels) (eg, about 8 cm in diameter and about 3 mm thick) were printed.
[0244] The printed disk was weighed prior to soaking (ie, initial weight). Immediately prior to weighing, any excess resin should be gently blotted from the printed disk using a Kimwipe.
[0245] Place the printed disc in a 24-well plate. Add IX DPBS++ to each well to approximately 5X the volume of the printed disc (i.e., the volume of an 8 mm x 3 mm printed disc is approximately 150 μL, therefore, approximately 1 mL of IX DPBS++ should be added to each well).
[0246] The printed disks should be weighed after soaking in IX DPBS++ for 24 hours at 37°C (ie, final weight after 24 hours). Immediately prior to weighing, any excess IX DPBS++ should be gently blotted off the printed disk using a Kimwipe.
[0247] The expansion % can be calculated as follows:
[0248] Fresh IX DPBS++ was added to each well. To continue the swelling test, the printed discs were soaked in IX DPBS++ at 37°C until 4 or 7 days later and weighed again (ie, final weight after 4 or 7 days).
[0249] Swelling data of AL62 bio-ink at 37°C
[0250] Compression test
[0251] Compression testing is discussed above and Figure 3A-3G-3 shown.
[0252] Fig.11 The synthetic AL60 (power 50mW / cm 2 , time is 1900ms), AL62 (power is 50mW / cm 2 , time is 750ms), AL62 (power is 150mW / cm 2 , time is 500ms), AL62 (power is 200mW / cm 2 Figure 2. Strain ε (%) vs stress σε (kPa) of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) 750,000 in Lung G1 (time 500 ms) bioink and Lung G1.
[0253] Fig. 12A Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in synthetic AL60 bioink.
[0254] Fig. 12B Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in synthetic AL61 bioink.
[0255] Fig. 12C It is synthetic AL62 (power 50mW / cm 2 ) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in bio-ink, showing the low cross-link density of the interpenetrating polymer networks of PEI in bio-ink.
[0256] Fig.12D It is synthetic AL62 (150mW / cm 2 ) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in bio-ink, showing the moderate cross-linking density of the interpenetrating polymer networks of PEI in bio-ink.
[0257] Fig.12E It is synthetic AL62 (200mW / cm 2 ) Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in bio-ink, showing the low cross-link density of the interpenetrating polymer networks of PEI in bio-ink.
[0258] AL60 Bio-ink Compression Data Area under the curve Maximum strain% 3796.09 286.60 4427.06 261.01 4435.10 286.20 2818.34 172.02 3811.92 132.85 4159.17 161.70 3907.94 216.73
[0259] AL62(50mW / cm 2 , 2750ms) Bio-ink compression data Area under the curve Maximum strain% 3224.50 183.94 1888.31 94.14 1902.74 85.04 2686.84 153.69 4899.90 256.91 2834.02 154.58 2906.05 154.72
[0260] AL62(150mW / cm 2 , 500ms) Bio-ink compression data Area under the curve Maximum strain% 3830.12 211.54 4232.07 233.76 5645.61 265.12 3123.30 172.02 3811.92 218.95 4959.65 263.49 4267.11 227.48
[0261] AL62(200mW / cm 2 , 2500ms) Bio-ink compression data
[0262] AL62 bio-ink at 50mW / cm 2 When printed, it produced a softer hydrogel than the AL60 bio-ink (stock solution); and the AL62 bio-ink was heated to 150 mW / cm 2 When printed, a tougher hydrogel was produced than the AL60 bio-ink (stock solution).
[0263] AL60 bio-ink (stock solution) at 150 mW / cm 2 and 200mW / cm 2When printing is performed, polyethyleneimine (PEI) polymer is incorporated.
[0264] Suture test
[0265] Using a 45mm gauge needle, pass the needle through the solid portion of the advanced manufactured hydrogel capsule. Inspect the hydrogel capsule for any cracking. The purpose of this test is to see if the hydrogel capsule can be sutured without cracking or unraveling.
[0266] Fig.13A The synthetic AL62 (power 50mW / cm 2 Figure 2. Suture test photo of the advanced fabricated interpenetrating polymer network (AM-IPN) of polyethyleneimine (PEI) in bio-ink (time 750ms), showing the low cross-linking density of the interpenetrating polymer network of PEI in bio-ink.
[0267] Fig. 13B The synthetic AL62 (power 100mW / cm 2 Photo of the stitching test of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyethyleneimine (PEI) in bio-ink (Figure 5, time 500ms), showing the low cross-linking density of the interpenetrating polymer networks of PEI in bio-ink.
[0268] Fig. 13C The synthetic AL62 (power 150mW / cm 2 Figure 2. Suture test photo of advanced fabricated interpenetrating polymer network (AM-IPN) of polyethyleneimine (PEI) in bio-ink (time 450ms), showing the moderate cross-linking density of interpenetrating polymer network of PEI in bio-ink.
[0269] AL62 bio-ink at 50mW / cm 2 and 100mW / cm 2 When printed, it failed the stitching test. However, AL62 bio-ink was able to 2 and 200mW / cm 2 When printing, pass the stitching test.
[0270] Polyvinylpyrrolidone (PVP)
[0271] In these examples, polyvinylpyrrolidone (PVP) polymer was incorporated into AI28 and AJ55 bioinks as shown below.
[0272] The PVP polymer has large side chains, and therefore, this polymer may cause the AI28 bioink to become stiff.
[0273] Polyvinylpyrrolidone (PVP) 130000
[0274] AI28 bio-ink (stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TMPTA912 2.85-3.15 NAP 1.52-1.68 UV386A 0.152-0.168 water 76.23-84.25 total 100
[0275] AL67 Bio-ink
[0276] AL68 Bio-ink
[0277] AL69 Bio-ink
[0278] AL70 Bio-ink
[0279] AI19 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 4.75-5.25 PEGDA6000 4.75-5.25 PEGDA575 2.85-3.15 NAP 1.9-2.1 UV386A 0.133-0.147 water 80.62-89.10 total 100
[0280] AL59 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 4.75-5.25 PEGDA6000 4.75-5.25 NAP 1.52-1.68 UV386A 0.114-0.126 water 75.75-83.73 total 100
[0281] AL71 Bio-ink
[0282] AI15 Bio-ink
[0283] AJ55 bio-ink (stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TMPTA912 1.9-2.1 NAP 0.95-1.05 UV386A 0.171-0.189 water 76.78-84.86 total 100
[0284] AI15 bio-ink (stock solution)
[0285] AL72 Bio-ink
[0286] AL73 Bio-ink
[0287] AL74 Bio-ink
[0288] AL75 Bio-ink
[0289] Rheological testing
[0290] Rheological tests were as discussed above and Figure 2A-2C-8 shown.
[0291] Fig.14 Shown is a graph of step time ts (s) vs storage modulus G' (kPa) for advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL68, AL69, AL70, AL72, AL73, AL74, and AL 75 bioinks.
[0292] Rheological data Bio-ink Start time Storage modulus at 50s AL68 3 16.77 AL69 3.5 17.97 AL70 2 18.71 AL72 3 17.39 AL73 3 20.67
[0293] AL68, AL70, AL72, AL73 and AL74 Bio-Ink Printing Settings for FS20 DLP 3D System Printers
[0294] Compression test
[0295] Compression testing is discussed above and Figure 3A-3G-3 shown.
[0296] Fig.15 Plots of strain ε (%) vs stress σε (kPa) for synthetic AL68 (3% triacrylate, 0.5% PVP), AL70 (3% triacrylate, 0.05% PVP), AL72 (2% triacrylate, 1% PVP), AL73 (2% triacrylate, 0.5% PVP), AL74 (2% triacrylate, 0.1% PVP) bioinks and advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinyl pyrrolidone (PVP) in Lung G1 are shown.
[0297] Fig.16A Photographs showing advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL68 bioink.
[0298] Fig. 16B Photograph of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL70 bioink.
[0299] Fig. 16CPhotograph of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL72 bioink.
[0300] Fig.16D Photograph of the advanced manufactured interpenetrating polymer network (AM-IPN) of polyvinylpyrrolidone (PVP) in the synthetic AL73 bioink.
[0301] Fig.16E Photograph of advanced manufactured interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL74 bioink.
[0302] AL68 Bio-ink Compression Data Area under the curve Maximum strain% 3204.69 199.05 4373.49 251.27 3337.19 184.19 2879.96 181.19 4374.83 260.40 4347.76 263.93 3752.98 223.47
[0303] AL70 Bio-ink Compression Data
[0304] AL72 Bio-ink Compression Data Area under the curve Maximum strain% 3423.97 209.84 3032.70 155.24 3281.38 207.95 3695.25 183.57 3231.84 188.50 3150.41 176.93 3302.59 187.01
[0305] AL73 Bio-ink Compression Data Area under the curve Maximum strain% 4027.78 255.23 3852.70 234.92 4421.14 207.95 3695.25 239.71 4094.71 236.51 3533.24 212.05 3937.47 231.061
[0306] AL74 Bio-ink Compression Data
[0307] Polyvinyl pyrrolidone (PVP) polymer was incorporated into AI28 bioink (stock solution) and AJ55 bioink (stock solution).
[0308] AL73 bioink has the best toughness and the highest maximum strain while maintaining flexibility.
[0309] Suture test
[0310] Using a 45mm gauge needle, pass the needle through the solid portion of the advanced manufactured hydrogel capsule. Inspect the hydrogel capsule for any cracking. The purpose of this test is to see if the hydrogel capsule can be sutured without cracking or unraveling.
[0311] Fig.17A Photographs showing stitching tests of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL68 bioink.
[0312] Fig. 17B Photographs showing stitching tests of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL70 bioink.
[0313] Fig. 17C Photographs showing stitching tests of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinylpyrrolidone (PVP) in synthetic AL73 bioink.
[0314] The AL70 bioink failed the suture test. However, the AL68 and AL73 bioinks passed the suture test.
[0315] Polyvinyl alcohol (PVA)
[0316] In these examples, polyvinyl alcohol (PVA) polymer was incorporated into AI28 bioink (stock solution) as shown below.
[0317] Polyvinyl alcohol (PVA) (2% PVP stock solution)
[0318] Polyvinyl alcohol (PVA) was added to water, heated at 200 °C, and mixed at 200 RPM before being incorporated into the bio-ink.
[0319] AI28 bio-ink (stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) HPA 9.5-10.5 PEGDA6000 4.75-5.25 TMPTA912 2.85-3.15 NAP 1.52-1.68 UV386A 0.152-0.168 water 76.23-84.25 total 100
[0320] AL76 Bio-ink
[0321] AL77 Bio-ink
[0322] Rheological testing
[0323] Rheological tests were as discussed above and Figure 2A-2C-8 shown.
[0324] Fig.18 Shown is a plot of step time ts (s) vs storage modulus G' (kPa) for advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in synthetic AL76 and AL77 bioinks.
[0325] Rheological data Bio-ink Start time(s) Storage modulus at 50s AL76 23 19.55 AL77 23 20.62
[0326] AL76 and AL77 Bio-Ink Printing Settings for FS20 DLP 3D System Printers
[0327] Compression test
[0328] Compression testing is discussed above and Figure 3A-3G-3 shown.
[0329] Fig.19 Shown is a plot of strain ε (%) vs stress σε (kPa) for the advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in the synthesis of AL76, AL77 bioinks, and Lung G1.
[0330] Fig. 20A The synthesis of AL76 (power 50mW / cm 2 Photograph of an advanced fabricated interpenetrating polymer network (AM-IPN) of polyvinyl alcohol (PVA) in bio-ink (Figure 2, time 1000ms), showing the low cross-linking density of the interpenetrating polymer network of PVA in the bio-ink. Fig. 20A As shown, at 50mW / cm 2 Polyvinyl alcohol (PVA) polymer was not incorporated into the AI28 bio-ink (stock solution) when printing was performed.
[0331] Fig. 20B The synthetic AL76 (power 100mW / cm 2 Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink (Figure 2, time 700 ms), showing the low to moderate cross-linking density of the interpenetrating polymer networks of PVA in bio-ink. Fig. 20B As shown, at 100mW / cm 2 For printing, polyvinyl alcohol (PVA) was incorporated into AI28 bio-ink (stock solution).
[0332] Fig. 20C The synthetic AL77 (power 100mW / cm 2 Photograph of an advanced fabricated interpenetrating polymer network (AM-IPN) of polyvinyl alcohol (PVA) in bio-ink (Figure 2, time 700 ms), showing the moderate cross-linking density of the interpenetrating polymer network of PVA in the bio-ink. Fig.19 C, with 100mW / cm 2 For printing, polyvinyl alcohol (PVA) was incorporated into AI28 bio-ink (stock solution).
[0333] Fig.21A The synthesis of AL76 (power 50mW / cm 2Photograph of an advanced fabricated interpenetrating polymer network (AM-IPN) of polyvinyl alcohol (PVA) in bio-ink (Figure 2, time 1000ms), showing the low cross-linking density of the interpenetrating polymer network of PVA in the bio-ink. Fig.21A As shown, at 50mW / cm 2 Polyvinyl alcohol (PVA) polymer was not incorporated into the AI28 bio-ink (stock solution) when printing was performed.
[0334] Fig.21B The synthesis of AL76 (power 50mW / cm 2 Photograph of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink (Figure 2, time 2500ms), showing low to moderate cross-linking density of the interpenetrating polymer networks of PVA in bio-ink. Fig.21B As shown, at 100mW / cm 2 For printing, polyvinyl alcohol (PVA) was incorporated into AI28 bio-ink (stock solution).
[0335] Fig. 21C The synthetic AL76 (power 100mW / cm 2 Photograph of an advanced fabricated interpenetrating polymer network (AM-IPN) of polyvinyl alcohol (PVA) in bio-ink (Figure 2, time 700 ms), showing the moderate cross-linking density of the interpenetrating polymer network of PVA in the bio-ink. Fig. 21C As shown, at 100mW / cm 2 For printing, polyvinyl alcohol (PVA) was incorporated into AI28 bio-ink (stock solution).
[0336] AL76 Bio-Ink Compression Data
[0337] AL77 Bio-ink Compression Data Area under the curve Maximum strain% 2483.12 159.09 2662.50 158.69 3775.61 237.50 3441.43 210.37 3403.70 222.92 2508.97 148.43 3046.06 189.50
[0338] At 50m / W / cm 2 Polyvinyl alcohol (PVA) polymer was not incorporated into the AI28 bio-ink (stock solution) during printing. However, at 100 m / W / cm 2 For printing, polyvinyl alcohol (PVA) polymer was incorporated into AI28 bio-ink (stock solution).
[0339] Suture test
[0340] Using a 45mm gauge needle, pass the needle through the solid portion of the advanced manufactured hydrogel capsule. Inspect the hydrogel capsule for any cracking. The purpose of this test is to see if the hydrogel capsule can be sutured without cracking or unraveling.
[0341] Fig.22A The synthetic AL76 (power 100mW / cm 2 Figure 2. Photo of the stitching test of advanced fabricated interpenetrating polymer networks (AM-IPNs) of polyvinyl alcohol (PVA) in bio-ink (Figure 2, time 700ms), showing the moderate cross-linking density of the interpenetrating polymer networks of PVA in the bio-ink.
[0342] Fig. 22B The synthetic AL77 (power 100mW / cm 2 Figure 2. Suture test photo of advanced fabricated interpenetrating polymer network (AM-IPN) of polyvinyl alcohol (PVA) in bio-ink (time 700ms), showing the moderate cross-linking density of interpenetrating polymer network of PVA in bio-ink.
[0343] AL76 and AL77 bioinks passed the suture test.
[0344] Interpenetrating polymer network mixture
[0345] In these examples, one or more of polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), and polyvinyl alcohol (PVA) polymers were incorporated into the synthetic bio-ink, as shown below.
[0346] polymer
[0347] Polyethylene oxide (PEO)
[0348] In these examples, polyethylene oxide (PEO) polymer was incorporated into AW55 bioink (stock solution) as shown below.
[0349] Polyethylene oxide 4000000 (0.5% PEO stock solution)
[0350] Polyethylene oxide 4000000 polymer was added to water, heated at 100 °C, and mixed at 600 RPM before being incorporated into the bio-ink.
[0351] Polyethylene oxide 400000 (0.5% PEO stock solution)
[0352] Polyethylene oxide 400000 polymer was added to water, heated at 100 °C, and mixed at 600 RPM before being incorporated into the bio-ink.
[0353] Polyethylene 100000 (0.5% PEO stock solution)
[0354] Polyethylene 100000 polymer was added to water, heated at 100°C and mixed at 600 RPM.
[0355] Polyvinyl alcohol (PVA)
[0356] Polyvinyl alcohol 100000 (4% PVA stock solution)
[0357] Polyvinyl alcohol (PVA) was added to water, heated at 200 °C, and mixed at 200 RPM before being incorporated into the bio-ink.
[0358] Polyethylene oxide 100000 (2% PEO stock solution)
[0359] Polyethylene oxide 100000 polymer was added to water, heated at 100 °C, and mixed at 600 RPM before being incorporated into the bio-ink.
[0360] Polyethylene oxide 200000 (2% PEO stock solution)
[0361] Polyethylene oxide 200000 polymer was added to water, heated at 100 °C, and mixed at 600 RPM before being incorporated into the bio-ink.
[0362] Ethylene oxide 4000000 (0.4% PEO stock solution)
[0363] Polyethylene oxide 1000000 polymer was added to water, heated at 100 °C, and mixed at 600 RPM before being incorporated into the bio-ink.
[0364] AW55 dual bio-ink (stock solution)
[0365] AW77 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 50 47.5-52.5 Triacetate PEO 100000 0.095-0.105 PEO 400000 0.095-0.105 PEO 4000000 0.095-0.105 water 47.22-52.19 total 100
[0366] AW78 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 Triacetate PEO 100000 0.475-0.525 PEO 400000 0.475-0.525 PEO 4000000 0.475-0.525 water 46.08-50.93 total 100
[0367] AW79 bioink (4% PVA stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 Triacetate 0.95-1.05 PVA 100000 4 11.88-13.13 water 34.87-38.54 total 100
[0368] AW80 bioink (4% PVA stock solution)
[0369] AW81 bioink (4% PVA stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 Triacetate PVA 100000 4 47.5-52.5 water total 100
[0370] AW82 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 PEO 4000000 9.5-10.5 water 38-42 total 100
[0371] AW83 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 PEO 4000000 4.75-5.25 water 42.75-47.25 total 100
[0372] AW84 bioink (2% PEO stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55Stock 47.5-52.5 PEO 100000 2 9.5-10.5 water 38-42 total 100
[0373] AW85 bioink (2% PEO stock solution)
[0374] AW86 bioink (2% PEO stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 PEO 200000 2 4.75-5.25 water 42.75-47.25 total 100
[0375] AW87 bioink (0.4% PEO stock solution) Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 PEO 4000000 0.4 4.75-5.25 water 42.75-47.25 total 100
[0376] AW93 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 PVP mixture 1.43-1.58 water 46.08-50.93 total 100
[0377] AW97 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 PVP mixture 1.43-1.58 HEMA 0.048-0.053 water 46.03-50.87 total 100
[0378] AW98 Bio-ink Reagents Molecular weight (MW) Registration Number Stock solution (%) quantity(%) AJ55 stock solution 47.5-52.5 Quinoline Yellow PVA 100000 47.5-52.5 water total 100
[0379] AW99 Bio-ink
[0380] AW99 Bio-ink (containing 2 / 0.3% PI / dye) printing settings for FS20 DLP 3D system printer
[0381] Expansion test
[0382] Observation of the swelling of the bioink hydrogel (dog-bone) for 24 h.
[0383] The AW93 bioink hydrogel (dog bone) swelled by about 30%, and therefore, the HPA dropped from 10% to 7%.
[0384] Compression test
[0385] Compression testing is discussed above and Figure 3A-3G-3 shown.
[0386] The compressive failure strength and strain are the values of the maximum stress (kPa) and maximum strain (%) at which the printed disk failed.
[0387] AW93 bio-ink (180mW / cm 2 , 1s)
[0388] AW99 bio-ink (180mW / cm 2 , 1s)
[0389] Fig.23A A graph showing the stress (kPa) of polyvinylpyrrolidone (PVP) in synthetic AW55, AW99, and AI28 bioinks.
[0390] Fig. 23B A graph showing the strain (%) of polyvinylpyrrolidone (PVP) in synthetic AW55, AW99, and AI28 bioinks.
[0391] Fig.23C A graph showing the Young's modulus (kPa) of polyvinylpyrrolidone (PVP) in synthetic AW55, AW99, and AI28 bioinks.
[0392] Fig.24 A photograph of a hydrogel (dog-bone) material is shown. Methods for preparing advanced manufactured interpenetrating polymer networks (AM-IPNs)
[0393] Methods for preparing advanced manufactured interpenetrating polymer networks (AM-IPNs) include: a) printing one or more of a primary polymer network, a secondary polymer network, and one or more crosslinks using synthetic bio-ink and 3D printing technology; b) assembling and / or printing AM-IPNs as described herein to form assembled AM-IPNs.
[0394] In an embodiment, the 3D printing technology is one or more of digital light projection printing (DLP), stereolithography (SLA) printing technology, extrusion 3D printing technology, or selective laser sintering 3D printing technology, or a combination thereof. In an embodiment, the 3D printing technology is digital light printing (DLP) printing technology. Methods using advanced manufactured interpenetrating polymer networks (AM-IPNs)
[0395] The method of using an advanced manufactured interpenetrating network (AM-IPN) includes: a) modifying the surface of the AM-IPN to attach small airway epithelial cells (SAEC) to form a modified AM-IPN.
[0396] In embodiments, the method further comprises: b) performing perfusion and ventilation using a modified AM-IPM, as described herein.
[0397] The embodiments and examples described herein are intended to best explain the present invention and its practical application, so that those skilled in the art can prepare and utilize the present invention. However, those skilled in the art will recognize that the foregoing description and examples are provided for illustration and example purposes only. The description is not intended to be exhaustive or to limit the present invention to the precise form disclosed. Many modifications and variations may be made according to the above teachings without departing from the spirit and scope of the following claims. The present invention is particularly intended to be as broad as the following claims and their equivalents.
[0398] Any reference to an embodiment or element or behavior of a system and method referred to herein in the singular may include an embodiment containing a plurality of such elements, and any reference to any embodiment or element or behavior in the plural may include an embodiment containing only a single element. References in the singular or plural are not intended to limit the currently disclosed systems or methods, their components, behaviors, or elements to a single or plural configuration. References to any behavior or element based on any information, behavior, or element may include an embodiment in which the behavior or element is based at least in part on any information, behavior, or element.
[0399] As used herein, the terms "approximately," "about," "substantially," and similar terms are intended to have a broad meaning consistent with the common and recognized usage by those of ordinary skill in the art to which the subject matter of the present disclosure belongs. Those skilled in the art who read the present disclosure should understand that these terms are intended to allow the description of certain features described and claimed without limiting the scope of these features to the precise numerical ranges provided. Therefore, these terms should be interpreted as indicating that insubstantial or inconsequential modifications or changes to the subject matter described and claimed are considered to fall within the scope of the present disclosure as described in the appended claims.
[0400] It should be noted that, as used herein, the term "exemplary" and variations thereof, used to describe various embodiments, are intended to indicate that these embodiments are possible examples, representatives, or illustrations of possible embodiments (and these terms are not intended to imply that these embodiments are necessarily the preeminent or best examples).
[0401] As used herein, the term "coupled" and its variants mean that two components are directly or indirectly connected to each other. Such connection can be stable (e.g., permanent or fixed) or removable (e.g., removable or releasable). Such connection can be achieved by coupling the two components directly to each other, or by coupling the two components to each other using a separate intermediate component and any additional intermediate components that are coupled to each other, or by coupling the two components to each other using an intermediate component that is integrally formed with one of the two components as a single entity. If "coupled" or its variants are modified by other terms (e.g., directly coupled), the general definition of "coupled" provided above will be modified by the ordinary language meaning of the other terms (e.g., "directly coupled" means that the two components are connected without any separate intermediate components), resulting in a narrower definition than the general definition of "coupled" provided above. Such coupling can be mechanical, electrical or fluid.
[0402] Any embodiment disclosed herein may be combined with any other embodiment, and references to "an embodiment," "some embodiments," "alternative embodiments," "various embodiments," "one embodiment," etc. are not necessarily mutually exclusive and are intended to indicate that a particular feature, structure, or characteristic described in connection with the embodiment may be included in at least one embodiment. As used herein, these terms do not necessarily all refer to the same embodiment. Any embodiment may be combined with any other embodiment, inclusively or exclusively, in any manner consistent with the aspects and embodiments disclosed herein.
[0403] References to "or" may be interpreted as inclusive, i.e., any term described using "or" may represent a single, more than one, or all of the terms. References to at least one of the terms listed with a conjunction may be interpreted as an inclusive "or" to indicate a single, more than one, or all of the terms. For example, references to "at least one of 'A' and 'B'" may include only 'A', only 'B', and both 'A' and 'B'. Elements other than 'A' and 'B' may also be included.
[0404] References to element positions herein (e.g., "top," "bottom," "above," "below") are only used to describe the orientation of the various elements in the drawings. It should be noted that the orientation of the various elements may be different according to other exemplary embodiments, and the present disclosure is intended to encompass such variations.
[0405] Although the figures and descriptions may illustrate a particular order of method steps, the order of these steps may be different from that depicted and described, unless otherwise specified above. In addition, unless otherwise specified above, two or more steps may be performed simultaneously or partially simultaneously. Such variations may depend on, for example, the selected software and hardware systems and the designer's choice. All of these variations are within the scope of the present disclosure. Similarly, the software implementation of the method may be implemented by standard programming techniques, using rule-based logic and other logic to implement various connection steps, processing steps, comparison steps, and decision steps.
[0406] Where technical features in the drawings, detailed description or any claims are followed by reference signs, these reference signs are introduced to improve the intelligibility of the drawings, detailed description and claims. Therefore, the presence or absence of these reference signs will not have any limiting effect on the scope of any claim element.
[0407] The systems and methods described herein may be implemented in other specific forms without departing from their characteristics. The foregoing embodiments are intended to illustrate rather than limit the systems and methods. Therefore, the scope of the systems and methods described herein is indicated by the appended claims rather than the foregoing description, and changes within the meaning and scope of the equivalents of the claims are also included therein.
Claims
1. An advanced manufactured interpenetrating polymer network (AM-IPN) comprising: primary polymer network; a secondary polymer network, wherein the secondary polymer network is bonded to the primary polymer network via one or more crosslinks, Wherein one or more of the primary polymer network, the secondary polymer network, and the one or more crosslinks are printed using synthetic bio-ink.
2. The AM-IPN according to claim 1, wherein the synthetic bio-ink comprises one or more of the following: HPA in an amount from about 0.5% to about 20%; PEGDA 6000 in an amount of about 0.5% to about 20%; TMPTA 912 in an amount of about 0.05% to about 3%; NAP in an amount of about 0.05% to about 3%; UV386A in an amount of about 0.0001% to about 0.5%; polymer in an amount from about 0.001% to about 2.0%; and Water, the amount of which serves as the balance.
3. The AM-IPN according to claim 2, wherein the polymer comprises one or more of the following: polyethylene oxide (PEO), polyethylene imine (PEI), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), and combinations thereof.
4. The AM-IPN of claim 3, wherein the polymer is PEO and has a molecular weight of about 100,000 to about 4,000,000.
5. The AM-IPN of claim 3, wherein the polymer is PEO in an amount of about 0.005% to about 1%.
6. The AM-IPN of claim 3, wherein the polymer is PEI having a molecular weight of about 25,000 to about 75,000.
7. The AM-IPN of claim 3, wherein the polymer is PEI in an amount of about 0.005% to about 1%.
8. The AM-IPN of claim 3, wherein the polymer is PVP having a molecular weight of about 1,000,000 to about 1,300,000.
9. The AM-IPN of claim 3, wherein the polymer is PVP in an amount of about 0.005% to about 2%.
10. The AM-IPN of claim 3, wherein the polymer is PVA having a molecular weight of about 89,000 to about 98,000.
11. The AM-IPN of claim 3, wherein the polymer is PVA in an amount of about 0.005% to about 2%.
12. The interpenetrating network of claim 1, wherein the synthetic bio-ink comprises one or more of the following: HPA in an amount from about 0.5% to about 20%; PEGDA 6000 in an amount of about 0.5% to about 20%; PEGDA 3400 in an amount of about 0.2% to about 15%; NAP in an amount of about 0.05% to about 3%; UV386A in an amount of about 0.0001% to about 0.5%; polymer in an amount from about 0.001% to about 2.0%; and Water, the amount of which serves as the balance.
13. The AM-IPN of claim 12, wherein the polymer comprises one or more of the following: polyethylene oxide (PEO), polyethylene imine (PEI), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), and combinations thereof.
14. The AM-IPN of claim 13, wherein the polymer is PEO and has a molecular weight of about 100,000 to about 4,000,000.
15. The AM-IPN of claim 13, wherein the polymer is PEO in an amount of about 0.005% to about 1%.
16. The AM-IPN of claim 13, wherein the polymer is PEI having a molecular weight of about 25,000 to about 75,000.
17. The AM-IPN of claim 13, wherein the polymer is PEI in an amount of about 0.005% to about 1%.
18. The AM-IPN of claim 13, wherein the polymer is PVP having a molecular weight of about 1,000,000 to about 1,300,000.
19. The AM-IPN of claim 13, wherein the polymer is PVP in an amount of about 0.005% to about 2%.
20. The AM-IPN of claim 13, wherein the polymer is PVA having a molecular weight of about 89,000 to about 98,000.
21. The AM-IPN of claim 13, wherein the polymer is PVA in an amount of about 0.005% to about 2%.
22. A method for preparing an advanced manufactured interpenetrating polymer network (AM-IPN), the method comprising: printing one or more of a primary polymer network, a secondary polymer network, and one or more crosslinks using a synthetic bio-ink and a 3D printing technique; and The AM-IPN is assembled and / or printed to form an assembled AM-IPN.
23. The method of claim 22, wherein the synthetic bio-ink comprises one or more of the following: polyethylene oxide (PEO), polyethyleneimine (PEI), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), and combinations thereof.
24. The method of claim 23, wherein the AM-IPN is heated at about 50 mW / cm 2 To about 400mW / cm 2 to print.
25. The method of claim 24, wherein the synthetic bio-ink comprises polyethylene oxide (PEO) in an amount of about 0.005% to about 1%, and wherein the AM-IPN is heated at 50 mW / cm 2 To about 300mW / cm 2 to print.
26. The method of claim 24, wherein the synthetic bio-ink comprises polyethyleneimine (PEI) in an amount of about 0.005% to about 1%, and wherein the AM-IPN is heated at about 150 mW / cm 2 To about 300mW / cm 2 to print.
27. The method of claim 24, wherein the synthetic bio-ink comprises polyvinylpyrrolidone (PVP) in an amount of about 0.005% to about 2%, and wherein the AM-IPN is heated at about 50 mW / cm 2 To about 300mW / cm 2 to print.
28. The method of claim 24, wherein the synthetic bio-ink comprises polyvinyl alcohol (PVA) in an amount of about 0.005% to about 2%, and wherein the AM-IPN is heated at about 100 mW / cm 2 To about 300mW / cm 2 to print.
29. The method of claim 13, wherein the 3D printing technology is one or more of digital light projection printing (DLP), stereolithography (SLA) printing technology, extrusion 3D printing technology, or selective laser sintering 3D printing technology, or a combination thereof.
30. The method of claim 13, wherein the 3D printing technology is digital light printing (DLP) printing technology.
31. A method of using an advanced manufactured interpenetrating polymer network (AM-IPN), the method comprising: The surface of the AM-IPN is modified to attach small airway epithelial cells (SAEC) to form a modified AM-IPN.
32. The method of claim 31 further comprising: The modified AM-IPM was used for perfusion and ventilation.